Learning to Unlearn : Decolonial Reflections from Eurasia and the Americas - Tlostanova, M. V. (Madina Vladimirovna); Mignolo, Walter (Book collections on Project MUSE., 2012)
"Addressing areas as diverse as the philosophy of higher education, gender, citizenship, human rights, and indigenous agency, and providing fascinating and little-known examples of decolonial thinking, education, and art, Madina V. Tlostanova and Walter D. Mignolo deconstruct the modern architecture of knowledge--its production and distribution as manifested in the corporate university. In addition, the authors dwell on and define the echoing global decolonial sensibilities as expressed in the Americas and in peripheral Eurasia"--Publisher's description